Peran Integrasi Artificial Intelligence dalam Pembelajaran Digital: Dampaknya Terhadap Efektivitas Kognitif dan Kreativitas Mahasiswa - Harini, Hegar; Utami, Purwani Puji; Ripki, Ahmad Jauhari Hamid; Khakim, Nor; Napis, Ahmad Durul (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the role of Artificial Intelligence (AI) integration in digital learning and its impact on students' cognitive effectiveness and creativity. A qualitative approach was employed using a literature review method and descriptive analysis of 32 scholarly articles published between 1983 and 2025, obtained from Google Scholar and various credible academic sources such as ResearchGate, ScienceDirect, Wiley Online Library, dan SpringerLink. The findings reveal that the integration of AI in learning positively contributes to enhancing cognitive effectiveness through adaptive, interactive, and personalized content delivery. On the other hand, student creativity is also fostered through AI support in the processes of idea exploration, concept visualization, and the strengthening of intrinsic learning motivation. These findings are supported by Cognitive Load Theory, the Componential Theory of Creativity, and Constructivist Theory, and are further reinforced by real-world case studies within higher education settings. Nevertheless, the effectiveness of AI is strongly influenced by digital literacy, pedagogical design, and users' ethical awareness.